Pengembangan Media Pembelajaran Interaktif Berbasis Android Pada Mata Pelajaran Alquran-Hadist Pada Pokok Bahasan Materi Infaq dan Sedekah Kelas VIII MTs - Khovadli Ocvando; Minhaji Minhaji; Abd Muqit; Luluk Maktumah (Edupedia : Jurnal Studi Pendidikan dan Pedagogi Islam, 2022)
This study aims to develop Android-based interactive learning media in al-Quran-Hadith subjects’ on the lesson of infaq and alms, class VIII MTS. This research use ADDIE (Analyse, Design, Development, Implementation, Evaluation). The results of this study 1) the majority of students already have an Android smartphone but it is still not optimal in its use in learning activities. In addition, educators are still less capable in developing interactive learning media, especially on android-based media. In this android-based interactive learning media, it contains video material for students, reviewing the material and making their own learning videos to be discussed later with the Kinemaster application tools, 2) the results of the assessment from media experts have an average score of 4,1 with category "Good," while the results of the assessment from material experts have an average score of 4,0 with category "Good." This means that the product of developing android-based interactive learning media on al-Quran-Hadith learning for class VIII on infaq and alms material is suitable to use in learning activities.